In vitro, Abortion and Euthanasia – Bioethics in “Gość Niedzielny’s” Discourse - Przybysz, Kinga (Media - Culture - Social Communication, 2019)
The author depicts “Gość Niedzielny’s” discourse in terms of controversial, bioethical issues, especially abortion, in vitro fertilization and euthanasia. Quantitative and qualitative discourse analysis was the main goal of the research described in the paper. The research results suggest that (during the last decade 2005–2015) bioethics has been eagerly described by newspaper journalists. The Catholic vision of bioethics has been presented as the universal and moral one. Radical law propositions have been created and opponents discredited.